Between the shield and the sword: equal marriage from the perspective of international public policy and international human rights law - Zelada, Carlos J. (2016)
In the last few years, an ever growing number of States have recognized same-sex marriage. For that reason, it is important to ask what would happen if two same-sex individuals that have legally contracted marriage in another countrywould sue for its recognition in Peru. The authors of this article study the courses ofaction available to legal operators facing this situation, in the context of the public policy exception and International Human Rights Law.For that purpose, they analize European and Inter-American case-law on the matter and offer a way forward on how to solve conflicts between foreign law, domestic law, and human rights.